Synergy Between Education and Industry: A Competency Development Model for Graduates at Islamic Universities in Cirebon - Asep Kurniawan; R. Agus Abikusna; Novianti Muspiroh; Bambang Firmansyah; Adinda Auliya Lu'lu'ah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2024)
This study aims to explore the development of graduate competencies in Islamic universities, the implementation of the Merdeka Belajar (Freedom to Learn) curriculum, and collaboration with the workforce using a qualitative Grounded Theory approach. A multisite study was conducted at State Islamic Cyber University of Syekh Nurjati Cirebon and Islamic University of Bunga Bangsa Cirebon, involving university leaders, lecturers, students, and other stakeholders. Data were collected through in-depth interviews, observations, documentation, and Focus Group Discussions, with triangulation techniques ensuring validity. Data analysis was carried out through open, axial, and selective coding to produce theories relevant to the research context. The findings reveal that both universities have unique approaches to preparing graduates for the workforce. State Islamic Cyber University of Syekh Nurjati Cirebon utilizes laboratory-based programs, fieldwork, and internships in relevant sectors. In contrast, Islamic University of Bunga Bangsa Cirebon emphasizes integrating theory and practice through collaboration with educational institutions and industries. Although the implementation of the Merdeka Belajar curriculum is not yet fully realized, progress has been made in providing flexible course options, community-based projects, and entrepreneurship initiatives. However, budget constraints and the socio-economic conditions of students pose significant challenges to competency development. The study also highlights the importance of strategic collaboration with the workforce to bridge the gap between education and industry needs. Programs such as Student Mobility, internships, and market-driven curricula contribute positively to graduates’ readiness for employment. The transformation of State Institute for Islamic Studies Syekh Nurjati into a State Islamic Cyber University of Syekh Nurjati Cirebon demonstrates significant potential in integrating digital technology to support learning and the creative economy. In conclusion, despite implementation challenges, both institutions strive to enhance their graduates' competitiveness through adaptive curriculum development, industry collaboration, and technology-based competency strengthening. The study recommends strengthening institutional policies and strategic budget management to overcome barriers and maximize students' potential in addressing workforce challenges